Carcinogenic and non-carcinogenic health risks of arsenic exposure in drinking water in the rural environment - D. Mahan; O. Waissbluth; D. Caceres (Global Journal of Environmental Science and Management, 2020)
Carcinogenic and systemic health effects of arsenic exposure in drinking water are well documented. This study estimated the risk associated with chronic consumption of water with high concentrations of arsenic in children and adults living in six Andean locations, in Chile. Concentrations of arsenic in the drinking water were analyzed between 2014 and 2017 based on health authority reports and data collected during this study. Average daily arsenic intake was estimated, and systemic (HQ) and deterministic carcinogenic risk (CR) indices were calculated using U.S. Environmental Protection Agency methodology. Threshold values ​​of HQ>1 and CR> 1 x 10–4 were considered to indicate high risk of adverse health effects. Four of the locations (Chucuyo > Putre > Humapalca = Visviri) had high concentrations of arsenic in the water, at levels 6.3–57.6 times the norm of 0.01 mg/L, Zapahuira and Belén, had values just below the threshold. Extremely high HQ values were estimated in children, at 1.3–119.8 times the threshold. Furthermore, CR values were several orders of magnitude (3.06–10790.6) above the tolerable value among all age strata. The locations studied have a high risk of adverse health effects from exposure to arsenic in drinking water. It is urgent to implement mitigation measures to improve water quality in these communities and to carry out probabilistic studies to provide more accurate assessment of exposure.